Cervical syringomyelia at the C7-C8 level presenting with bilateral scapular winging - Niedermaier, Nikolaj; Meinck, Hans-Michael; Hartmann, Marius (Journal of neurology, neurosurgery, and psychiatry, 2000)
Scapular winging is a neurological sign specifically caused by weakness of the serratus anterior, trapezius, or rhomboid muscles.1 2 Trauma, complications of surgery, myopathies, or peripheral nerve diseases are the major causes. We report on a patient with bilateral scapular winging as the presenting symptom of cervical syringomyelia at the C7-C8 spinal cord segments. - - This 38 year old carpenter complained of progressive involuntary movements of the right arm associated with arm and shoulder pain for the past 3 years. Involuntary movements were provoked by writing and similar activities. The patient was suspected of having a psychogenic movement disorder. - - Examination disclosed normal cranial nerve functions, mild hypertrophy of the right arm muscles, bilateral scapular winging of the serratus …
Gesehen am 04.03.2021